Cross-Sectional Study to Estimate the Prevalence of Familial Hypercholesterolemia in Selected Regions of the Russian Federation: Relevance, Design of the Study and Initial Characteristics of the Participants - A. N. Meshkov; A. I. Ershova; S. A. Shalnova; A. S. Alieva; S. S. Bazhan; O. L. Barbarash; D. Y. Bogdanov; I. A. Viktorova; Yu. I. Grinshtein; D. V. Duplyakov; O. N. Kalachikova; A. V. Kontsevaya; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To study the prevalence of familial hypercholesterolemia (FH), the characteristics of the clinical features and treatment of the disease in selected regions of the Russian Federation, this article describes the design and initial characteristics of patients included in the study.Material and methods. The study participants were selected among those included in the study “Epidemiology of cardiovascular risk factors and diseases in the regions of the Russian Federation” (ESSE-RF) in different regions of the Russian Federation. The study included individuals with lowdensity lipoprotein cholesterol (LDL-C) levels >4.9 mmol/l or LDL-C levels >1.8 mmol/l, but ≤4.9 mmol/l during statin therapy, according to the data obtained in the ESSE-RF study. These persons are invited for examination and questioning by experts in the field of FH diagnostics. On the basis of the survey data and provided medical documentation, the following information is collected: age, sex, smoking status, presence of hypertension, history of coronary artery disease, stroke, atherosclerosis of cerebral and peripheral arteries, LDL-C level, type, volume and duration of lipid-lowering therapy throughout life, presence and dates of secondary causes of hyperlipidemia, information about the family history of development of early cardiovascular diseases and atherosclerotic diseases, increased levels of LDL-C in relatives of the 1st and 2nd degree of kinship. All patients are examined for the presence of tendon xanthomas (Achilles, metacarpal, elbow, knee tendons) and Corneal arcus. During the visit, blood is taken for subsequent biobanking, measurement of current blood lipid levels, elimination of secondary forms of hypercholesterolemia (for subsequent determination of liver enzymes, thyroid stimulating hormone) and genetic testing. The diagnosis of FH is based on Dutch Lipid Clinical Network Criteria (DLCN). Besides, all participants in the study are tested for compliance with the diagnosis of FH according to Simon Broome criteria. All patients with a definite or probable diagnosis of FH according to DLCN or Simon Broome criteria are subjected to ultrasound examination of carotid, femoral arteries and heart and molecular genetic testing for LDLR, APOB and PCSK9 gene variants.Results. Out of 16 360 participants of the ESSE-RF study in 10 regions, 1787 people (10,9%) met the criteria for inclusion in this study. Among them, men accounted for 35.4%, of which 1150 (7%) patients had a LDL-C level >4.9 mmol/l and 637 (3,9%) had a LDL-C level from 1,81 mmol/l to 4.9 mmol/l during lipid-lowering therapy. When compared to the original cohorts of participants from the 10 regions as compared to 3 previously surveyed regions and selected sub-groups within these cohorts we observed significant differences in several parameters such as age, total cholesterol level, triglycerides, LDL-C, the frequency of cardiovascular diseases, that may indicate regional differences in FH prevalence.Conclusion. The analysis of clinical data of the participants of the ESSE-RF study shows that more than 10% of individuals require an additional examination to verify the FH diagnosis, and regional differences in the FH prevalence are possible.